The current status and trend of the functional magnetic resonance combined with stimulation in animals - Huang, Jiayang; Zhang, Yusi; Zhang, Qi; Wei, Linxuan; Zhang, Xiwen; Jin, Caiping; Yang, Junchao; Li, Zuanfang; Liang, Shengxiang (Frontiers in Neuroscience, 2022)
As a non-radiative, non-invasive imaging technique, functional magnetic resonance imaging (fMRI) has excellent effects on studying the activation of blood oxygen level and functional connectivity of brain in human and animal models. Compared with resting-state fMRI, the fMRI combined with stimulations could be used to assess the activation of specific brain regions and the connection of specific pathways, and achieve better signal capture with clear purpose and more significant results. Various fMRI methods and specific stimulation paradigms have been proposed to investigate the brain activation in specific state, including electrical stimulation, mechanical stimulation, visual stimulation, olfactory stimulation, direct brain stimulation and so on. In this review, the studies on animal brain activation using fMRI combined with different stimulation methods were retrieved and the instruments, experimental parameters, anesthesia state, and animal models in different stimulation conditions were summarized. The findings would provide a reference for those studies on estimating specific brain activation by using fMRI combined with stimulations.